Discovering Hidden Pattern in Social Media Data to Empower MSMEs in The Digital Economy - Indira Nuansa Ratri; Arum Andary Ratri; Junaedi Adi Prasetyo (Dinasti Publisher, 2025)
The digital economy presents new opportunities and challenges for micro, small, and medium enterprises (MSMEs). This study explores hidden patterns in social media data to strengthen MSMEs in the culinary, tourism, and fashion-textile sectors. Using a mixed-methods approach, quantitative data mining of leading brands’ social media was combined with qualitative validation through interviews with nine MSME representatives. Quantitative analysis revealed key engagement trends and content strategies, while qualitative insights confirmed their relevance and feasibility for SMEs. The integration of findings demonstrates that social media analytics can guide SMEs in enhancing digital presence, improving competitiveness, and adapting to shifting consumer behaviors. The study contributes practical recommendations for MSMEs while positioning social media as a strategic tool for sustainable growth in the digital era.